Formulation of Gelatin-Based Wheatgrass Leaf Juice Gummy Jellies with Antioxidant and the Analyses of Physicochemical and Texture Properties as well as Evaluate the Nutritional Property of Selected Formulation - Jaroennon, Pattamaporn; Nuanchankong, Jutawan; Manakla, Sakunta (Journal of Food Health and Bioenvironmental Science, 2023)
The aim of this study was to develop gummy jellies from wheatgrass leaf juice, assess the antioxidant activity of wheatgrass, and study the effects of gelatin (10, 20, 30 and 40% of honey weight) on the physicochemical properties and texture using different techniques (warm and hot), as well as evaluate the nutritional property of selected formulation. The antioxidant activity of wheatgrass was determined using the DPPH assay. The 50% effective concentration (EC50) was 23.42±1.13 mg sample/mL. This concentration was then used in formulation of gummy jellies. The samples were investigated for moisture, water activity, pH, color, and texture. The moisture, water activity and pH were in the range of 0.66±0.07 - 6.20±0.62 %, 0.72±0.03 - 0.87±0.02 and 4.76±0.08 - 5.92±0.04, respectively. The result suggested that gummy jellies had low moisture, water activity and pH, particularly the 10% honey weight of gelatin concentration using the hot technique (H1 formulation). These low values contribute to potentially increase in their shelf life. The gummy jellies were red-yellowish in color. The texture of the H1 formulation was not significantly different (p>0.05) in hardness, gumminess and chewiness compared to 20-30% honey weight of gelatin using both hot and warm techniques. Therefore, the H1 formulation was selected for the analysis of nutritional properties. The energy of the H1 formulation was 56 kcal/50 g per one serving. Most of the energy of the gummy jelly came from sugar (18 g). According to the recommendation by WHO, adults and children should consume less than 25 grams of sugar per day to reduce the risk of NCDs. Therefore, the gummy jelly is suitable for less than 2 servings per day.